Generational Cohorts: An Empirical Investigation into the Indian Millennial’s Shopping Characteristics. - Siji, Dr. Smitha (The journal of contemporary issues in business and government, 2021)
Purpose India, one among the rapidly growing economies of the world, has a growing luxury market and it houses the largest youth population called the ‘millennial’. Looking at all these factors plus the tendency of the millennial to be driven by status, this study was conducted with a purpose to examine the millennial consumer’s relationship between “Status Consumption and Consumer Styles Inventory.” Method A descriptive research was designed for the study. 240 millennial consumers were selected through convenience sampling technique. The research instrument was a questionnaire consisting of 24 statements measuring Consumer Styles Inventory using Sproles and Kendall (1986) scale and Status Consumption by Eastman et al. (1999) scale. Findings All the facets in the Consumer Style Inventory had a significant influence on Status Consumption. Brand Consciousness and Novelty consciousness has the biggest influence on Status consumption. But an inverse relationship existed between status consumption and recreational shopping. Practical Implications This study found that the millennial either prefers to stick to good brands or they continually seek something new. Thus this is a significant insight to manufacturers and retailers about the millennial. It will help them in designing their marketing strategies for the millennial as they happen to be a significant entity in today’s market. Originality/Value There are not much studies on the shopping styles of the Indian Millennial and hence the findings of this study is very much valuable to the marketers operating in the Indian luxury market.